Figury grozy w literackiej i malarskiej twórczości Zdzisława Beksińskiego - Kubińska, Bogna (Załącznik Kulturoznawczy, 2021)
The author of this article focuses on the category of dread which is characteristic of Beksiński’s works. It is an original phenomenon because of the tools that create it and its influence on the poetics of the artistic text. The most important areas of the artist’s literary works and paintings in which he operated with dread, were space, characters and colors. Due to the similarity of means of expression shaping dread in stories and paintings, one can speak of transmedia figures of dread in Beksiński’s work, i.e. metaphor, exaggeration, oxymoron, repetition, animation, play with the perspective and points of view. These figures coexist with each other, interact with each other in the process of creating a unique world of dread, characteristic only to Beksiński. On the other hand, dread itself affects the tools that make it up and transforms the effect of their operation. The author of the article calls such a phenomenon ‘acquainted dread’ – the action of the figures used, initially causing dread, is reversed and means that the presented elements – despite the clear features causing fear – cease to be its source for the recipient.